Systematic Triggering of Large Earthquakes by Karst Water Recharge: Statistical Evidence in Northeastern Italy - Bragato, Pier Luigi (Frontiers in Earth Science, 2021)
It is known that surface water accumulation by natural or anthropic causes like precipitation and reservoir impoundment can trigger earthquakes. The phenomenon is amplified and sped up in karst areas, where fracture systems can store large quantities of water and facilitate its percolation to seismogenic depths, increasing both elastic stress and pore pressure on pre-existent faults. The present work explored the possibility that this mechanism had systematically triggered major earthquakes in northeastern Italy, where seismicity is concentrated along the pre-Alpine thrust belt, characterized by the alignment of a series of karst massifs. The time occurrence of damaging and destructive earthquakes (moment magnitude Mw between 4.8 and 6.4) since 1901 was compared with the evolution of the Palmer Drought Severity Index (PDSI), an index of soil moisture that summarizes precipitation and, through temperature, water evaporation. Statistical analysis based on the bivariate Ripley’s K-function shows a significant time correlation between earthquakes and the peaks of PDSI since 1934, with the two strongest earthquakes (1936 Alpago-Cansiglio earthquake and 1976 Friuli earthquakes, Mw 6.1 and 6.4, respectively) placed by the two PDSI maxima. The analysis was extended back in time to the last millennium, showing a time correlation between the occurrence of destructive earthquakes (Mw≥6.2) and the peaks of ice extension in the European Alps, assumed as a proxy for groundwater accumulation in the study area. This evidence presented herein coupled with geological characteristics of the area and recent observations on large crustal deformations induced by heavy precipitation suggests that, if sc-PDSI is a valid ground water indicator, karst water recharge may play a role in triggering major earthquakes in northeastern Italy, also relating their occurrence to the large scale climate changes affecting precipitation and evaporation.